Seeking the exclusive binding region of phenylalkylamine derivatives on human T‐type calcium channels via homology modeling and molecular dynamics simulation approach. Issue 3 (13th May 2021) - Lu, You; Li, Ming; Lee, Gi Young; Zhao, Na; Chen, Zhong; Edwards, Andrea; Zhang, Kun
Abstract: Pharmaceutical features of phenylalkylamine derivatives (PAAs) binding to calcium channels have been studied extensively in the past decades. Only a few PAAs have the binding specificity on calcium channels, for example, NNC 55‐0396. Here, we created the homology models of human Cav 3.2, Cav 3.3 and use them as a receptor on the rigid docking tests. The nonspecific calcium channel blocker mibefradil showed inconsistent docking preference across four domains; however, NNC 55‐0396 had a unique binding pattern on domain II specifically. The subsequent molecular dynamics (MD) simulations identified that Cav 3.1, Cav 3.2, and Cav 3.3 share domain II when Ca 2+ appearing in the neighbor region of selective filters (SFs). Moreover, free‐energy perturbation analysis suggests single mutation of lysine at P‐loop domain III, or threonine at the P‐loop domain II largely reduced the total amount of hydration‐free energy in the system. All these findings suggest that P‐loop and segment six domain II in the T‐type calcium channels (TCCs) are crucial for attracting the PAAs with specificity as the antagonist. Abstract : Predicted Ca 2+ interaction domains during 200 ns simulation period. For α1 H, Ca 2+ ions are more likely to dock domain I (A) and II (B); however, for α1 I: Ca 2+ ions are more likely to dock domain II (C) and IV (D). ​